Study on the impact of the Tri An reservoir on its downstream groundwater level regime - Hoàng, Nguyễn Văn; Thuận, Đinh Văn; Rỡi, Nguyễn Đức; Lương, Lê Đức (Vietnam Journal of Earth Sciences, 2013)
This paper presents groundwater modeling works for the south downstream Tri An reservoir area to address the impact of the reservoir on groundwater level regime. Two models have been carried: one for the whole large downstream area to study the regional groundwater level regime and another for smaller area immediate downstream the reservoir to study in more details the impact on Pleistocene basalt aquifer. The results have shown that for many years of the reservoir operation with water level ranging from death level to maximal flood level, the reservoir has impact only on distance of about 15km downstream. The annual reservoir water level fluctuation has impact only in short distance from the reservoir about 8km to cause groundwater level fluctuation magnitude of about 0.1m. For the Pleistocene basalt aquifer in the south, the reservoir has causing water level increase of about 30m (in distance of about 500m from the reservoir) to 1m (in distance of about 8km from the reservoir). With this water level rise and/of aquifer thickness increase over more than 200km2 in the south downstream, the groundwater exploitation reserve would dramatically increase.